An exploratory fNIRS study with immersive virtual reality: a new method for technical implementation - Seraglia, Bruno; Gamberini, Luciano; Priftis, Konstantinos; Scatturin, Pietro; Martinelli, Massimiliano; Cutini, Simone (Frontiers in Human Neuroscience, 2011)
For over two decades Virtual Reality has been used as a useful tool in several fields, from medical and psychological treatments, to industrial and military applications. Only in recent years researchers have begun to study the neural correlates that subtend virtual reality experiences. Even if the fMRI brain image technique is the most common and used technique, it suffers several limitations and problems. Here we present a methodology that involves the use of a new and growing brain imaging technique, fNIRS functional Near-infrared Spectroscopy, while participants experience immersive virtual reality. In order to allow a proper fNIRS probe application, a custom-made virtual reality helmet was created. To test the adapted helmet, a virtual version of the line bisection task was used. Participants could bisect the lines in a virtual peripersonal or extrapersonal space, through the manipulation of a Wiimote controller in order for the participants to move a virtual laser pointer. Although no neural correlates of the dissociation between peripersonal and extrapersonal space were found, a significant hemodynamic activity with respect to the baseline was present in the right parietal and occipital areas. Both advantages and disadvantages of the presented methodology are discussed.